Implikasi Isu Poligami dalam Menimbulkan Polemik Rumah Tangga - Hardianto, Tarmizi; Arifin Badri, Muhammad (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2023)
The purpose of this research is to find out the issue of polygamy in the household, whether it has implications for causing household polemics or not, what are the main factors that cause polemics on the issue of polygamy, and how to deal with the issue. Issues are news circulating in social relations. In the issue there is information that can be true and can be false. The ability to sort information could prevent conflict. This research uses a descriptive analysis research type with a qualitative approach. The results: (1) the issue of polygamy that was not true had ever happened to the Prophet Ṣallá Allāh ʻalayhi wa-sallam, and also the issue of polygamy plans had ever happened to Ali bin Abi Talib Raḍī Allāh ʻanhu with the daughter of Abu Jahal was proven to be true, (2) polemic factors after the issue of the polygamy of Rasulullah Ṣallá Allāh ʻalayhi wa-sallam was motivated by jealousy and indications of a haste to believe the news, as well as the rejection of Rasulullah Ṣallá Allh ʻalayhi wa-sallam regarding Ali bin Abi Talib Raḍī Allāh ʻanhu’s polygamy plan was an attempt to cover up slander against the religion of Fatimah Raḍī Allāh ʻanhā , (3) the issue of polygamy can have implications for causing polemics in the household, (4) clarification and tabayun play an important role so that there are no wrong attitudes and can also reduce conflict from issues.